What all physicians should know about women’s health: a Delphi study - Susanna Price; Eva Gerdts; Julien Mazières; Alexandra Kautzky-Willer; Fedde Scheele; Chiara Benedetto; Kerry Wilbur; Gertraud Stadler; Marieke Wermer; Jeanine Roeters van Lennep; Merel H de Heer-Koster; Vesna Bjegović-Mikanović; et al. (BMJ Public Health)
Objectives Over the past few decades, knowledge of women’s health regarding sex and gender differences in health has increased but transfer of these new insights into medical education and clinical practice is lagging, resulting in substandard care for women compared with men. This study aimed to reach consensus on what all physicians taking care of women should know about women’s health.Methods A Delphi study was executed involving statements prepared by experts in women’s health across 10 medical specialties and a patient advisory board. Participants were recruited from Europe and Northern America through the experts’ networks and snowball sampling. Participants voted IN/OUT on each statement based on its perceived relevance and feasibility for general physician knowledge, regardless of specialty. The statements were ranked according to a >80% consensus in the first Delphi round and a 4-point Likert scale in the second Delphi round.Results In the first round, 44 participants fully completed the survey. 18 statements progressed to the second round, in which four additional statements were included based on participant suggestions. In the final round, 35 responses on the 22 selected statements resulted in consensus on 18 statements of the highest importance, within the following domains: the societal position of women in health, patient perception of disease and treatment, differences in symptomatology, pharmacological considerations and the impact of the female life cycle on health and disease.Conclusion Consensus was reached on the top priority clinical conditions and public health issues in women’s health, resulting in a list of 18 statements on women’s health that every physician caring for women should know, regardless of specialty. There was also consensus on the importance of incorporating these insights into medical education. The next step involves implementing women’s health education in medical schools, postgraduate education and continuing education for medical specialists.